Manajemen Program Seni Baca Al – Qur’an di MTSN Toba Samosir - Ayu Mardiyatin Zanah Nurhikmah; Abd Rahman (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research aims to find out how the Al-Qur'an reading art program is managed at MTsN Toba Samosir and to find out how the planning, organization, implementation and evaluation of the Al-Qur'an reading art program at MTsN Toba Samosir is carried out. This research uses qualitative methods, namely observation, interviews and direct documentation. The results of the research in the Al-Quran reading arts program at MTsN Toba Samosir have not gone well because some of the students are not yet familiar with reading the Al-Qur'an and some of the students who can read the Al-Quran are not yet in accordance with the rules of recitation science. . Therefore, the planning, organization, implementation and evaluation is intended to see and improve what are obstacles in the Al-Qur'an reading arts program activities. From the results and discussion, researchers can conclude that the Al-Quran reading arts program at MTsN Toba Samosir is not only learning about Qur'anic recitations, but the school created this activity to eradicate Qur'an illiteracy among students and improve the quality of students in reading Al-Qur'an.